Role of Frailty Scoring in the Assessment of Perioperative Mortality in Surgical Management of Tuberculous Spondylodiscitis in the Elderly. Issue 7 (October 2018) - Shah, Kunal; Kothari, Manish; Nene, Abhay
Study Design: Retrospective study. Objectives: Treatment of spinal tuberculosis in the elderly involves consideration of compromised physiology, which often poses a clinical challenge to the surgeons to balance surgical safety versus deteriorating function. Frailty scoring has been reported as an effective tool to predict mortality and morbidity in cardiovascular surgery and recently in hip fractures. Its use in spinal surgery is scarcely reported. Methods: We included elderly patients operated for spinal tuberculosis. Demographic, clinical and radiological profile with operative details of instrumentation, blood loss, surgical duration and mortality were noted. Modified frailty score (MFS) was calculated for each patient. There were 26 patients (males 9, females 17) with a mean age of 73.2 years. The patients were divided into those with 30-day postoperative mortality (M) and those who survived (S). The null hypothesis was that the MFS was comparable in both the groups. Results: The M group had 5 patients (19.2%) and the S group consisted of 21 patients. There was no statistical difference between the groups with regard to mean age, sex, number of medical comorbidities, ASA (American Society of Anesthesiologists) grade, Frankel grade C or worse, blood loss, and operative time. The mean MFS in M group was 5 and in S group was 1.8, which was statistically significant ( P < .001). Conclusions: Higher MFS is associated with postoperative 30-day mortality in the elderly patients with spinal tuberculosis undergoing surgery. It can be used as a guide to predict 30-day postoperative mortality in these patients.